DRUG UTILIZATION PATTERN IN GERIATRIC PATIENTS ATTENDING OUT PATIENT DEPARTMENT AT RURAL TERTIARY CARE HOSPITAL IN MAHARASHTRA. - Nishandar, Tushar B; Kale, Anand S; Pise, Harshal N (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To observe a prescription pattern in elderly patients attending outpatient department (OPD) and evaluating prescriptions according to theWorld Health Organization (WHO) prescription indicators. Methods: A cross-sectional observational study was conducted from July to September 2015. Patients of either gender, age 60 years or more, attending OPD in tertiary care hospital were included in the study. Prescriptions of medical practitioners were collected and evaluated for demographic data and the WHO drug prescribing indicators. Results: A total of 600 patients were enrolled in the study. The majority of the patients were in the age group 60-69 years (66.33%) with male preponderance (61%). The average number of drugs per prescription was 3.41. Out of 2045 drugs prescribed, 1261 drugs (61.66%) were prescribed by their generic name and 784 drugs (38.33%) were prescribed by their brand name. 1700 drugs (83.12%) prescribed were from the WHOs essential medicines list 2015. Total encounters involving injectable usage were 0.15%. Drugs acting on the cardiovascular system (21.12%) were the most frequently prescribed, followed by nonsteroidal anti-inflammatory drugs (NSAIDs) (20%). Ranitidine (16.62%) is the most frequently prescribed drug.Â Conclusions: In this study, drug prescription pattern was rational as per the WHO drug prescribing indicators. However, issues such as polypharmacy and inaccuracies of dose and duration were seen. Keywords: Drug utilization study, Geriatric, Outpatient department, Rational use of medicines.